The influence of nitrogen-fertilizer and harvest time on the productivity of Thymus vulgaris L. - Omidbaigi, R.; Rezaei Nejad, A. (International Journal of Horticultural Science, 2000)
The influence of nitrogen-fertilizer applied in 0, 50, 100 and 150 kg/ha dosages, as well as the time of the harvest carried out in full flowering and early fruit set stages were studied on the herb and essential oil production of garden thyme (Thymus vulgaris L.). The small plot experiment was installed in the Experimental Field of Tarbiat Modarres University near Teheran, under sandy loam soil conditions. On the basis of the results the nitrogen-fertilizer had a significant effect on the dry-matter production of the species: the herb yield, calculated on one hectare, increased from 671.88 kg up to 1021.00 kg value as a result of 150 kg nitrogen dosage. The essential oil yield proved to have a similar tendency because neither the accumulation level of essential oil, nor the ratio of thymol were effected by the nutrient supply. Analyzing the effect of harvest time changes in both dry-mass production and essential oil accumulation were observed. The highest herb yield (1238.20 kg/hectare) was obtained in early fruit set, when about.50 per cent of fruits reached their full size in the inflorescence. The accumulation level of essential oil also reached its maximum at the sane development stage, showing 0.75 per cent value, which is about two fold higher comparing to the accumulation level was measured at the time of full flowering (0.41 %).